Platelet inhibition with prasugrel (CS‐747) compared with clopidogrel in patients undergoing coronary stenting: the subset from the JUMBO study - Serebruany, V L (BMJ Group, 2006)
BACKGROUND: Based on the preclinical and phase 1 studies, prasugrel, a novel platelet ADP P2Y12 receptor blocker, may be a more potent platelet inhibitor than clopidogrel. This study compared the antiplatelet properties of prasugrel in a small subset of patients enrolled in the JUMBO trial, and compared with historic clopidogrel treated controls. METHODS AND RESULTS: Nine patients undergoing coronary stenting were randomised to one of three arms of prasugrel (40 mg loading, and 7.5 mg maintenance, n = 1; 60/10 mg, n = 4; or 60/15 mg, n = 2), or clopidogrel (300/75 mg, n = 2). Aspirin and GP IIb/IIIa inhibitors were permitted. Platelet activity was assessed at baseline, at 4, and 24 hours, and at 30 days after stent implantation in substudy participants, and compared with 124 historic controls who received clopidogrel. Independent of the loading, or maintenance dose, patients treated with prasugrel exhibited significantly more potent platelet inhibition as determined by ADP, and collagen induced aggregation, Ultegra Analyser, and surface expression of PECAM‐1, GPIIb/IIIa antigen, and activity with PAC‐1 antibody, GPIb, P‐selectin, CD40‐ligand, GP37, and thrombospondin receptor expression when compared with those treated with clopidogrel. There were no differences between antiplatelet agents with regard to vitronectin, LAMP‐1, PAR‐1 (intact and cleaved epitopes) thrombin receptor expression, or formation of platelet‐monocyte microparticles. Expression of GPIIb antigen, vitronectin, and LAMP‐3 receptor were not affected by both agents. Two patients treated with prasugrel 10 mg/daily exhibited complete inhibition of collagen induced aggregation at 30 days. CONCLUSION: At the dosing regimens chosen in the JUMBO trial, it seems that prasugrel is a more potent antiplatelet agent than clopidogrel. Two episodes of profound platelet inhibition, which are not seen with clopidogrel, raise the possibility of higher bleeding risks especially during long term prasugrel use. Whether stronger platelet inhibition will yield better clinical outcomes and/or increased bleeding remains to be determined in an ongoing comparative phase 3 superiority trial (TRITON).